Performing National Identity in the Yellow River Piano Concerto: A Reflexive Practice-Led Study - Yan Junyu; P’ng Tean Hwa; Cheong Ku Wing (Universitas Negeri Semarang, 2026)
This study examines how national and self-identity are articulated through the performance of the Yellow River Piano Concerto. Using a practice-led and reflexive approach, the research traces how interpretive decisions emerge and evolve through rehearsal documentation, annotated scores, and self-narrative journals. These materials allow close observation of how technical, expressive, and communicative choices shape the performer’s engagement with cultural meaning. The findings highlight three key insights. First, reflexive practice helps the performer recognize how personal history, cultural memory, and artistic intention inform interpretive choices. Second, the performance process highlights recurring themes such as patriotic expression, historical imagery, and ideological negotiation. These elements jointly shape the enactment of national identity. Third, the study proposes the TEC framework (Technique, Expression, Communication) to describe how national identity is embodied and communicated through performance. Overall, the research shows that performing the Yellow River Piano Concerto renews and reshapes its cultural associations, enabling national sentiment to be expressed through evolving interpretive practice. The findings underscore the performer’s active role in constructing meaning and suggest that the TEC framework may be valuable for future studies on national identity in musical performance.